Polisi Dalam Mewujudkan Keamanan Dan Ketertiban Masyarakat Di Era Digital: Studi Kasus Pencemaran Nama Baik - Muhammad Naufal Alif Riyadi; Wahyu Prawesthi; Subekti .; Fathul Hamdani (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2022)
The development of information and communication technology has brought about significant changes in people's lives, including in legal and security aspects. Social media is now a primary means of communication accessible to various groups, but this convenience also opens up opportunities for crimes such as defamation. This study aims to analyze the police's handling of defamation cases via social media in the digital era and examine the forms of legal accountability for perpetrators. Using normative juridical research methods with legislative, conceptual, and case study approaches, this study examines relevant regulations, such as the Criminal Code (KUHP) and the ITE Law, particularly articles on insults and hate speech. The results show that the police play a crucial role in investigating and prosecuting cybercrimes, although handling them faces technical and social challenges. Law enforcement against defamation requires careful evidence, including the perpetrator's malicious intent and the impact on the victim. Furthermore, personal, family, educational, and social factors contribute to the rise in hate speech cases on social media. This study recommends increasing police capacity in digital technology and educating the public to be more judicious in using social media to maintain security and order in the digital era.